Evaluating The Swedish Approach to Motivating Improved Work Safety Conditions on Farms: Insights from Fear Appeals and the Extended Parallel Processing Model. - Alwall Svennefelt, Catharina; Hunter, Erik; Lundqvist, Peter (Journal of Agromedicine, 2018)
Farm work safety intervention programs based on educating and informing have been criticized for not demonstrably improving work safety. We argue that these criticisms are misplaced and that the problem with educating and informing lies not necessarily in the tool, but rather in its implementation. We arrive at this conclusion by systematically investigating eight of the largest farm work safety interventions in Sweden. In particular, we describe how they use fear and other emotional appeals in their communications in an attempt to motivate improved work safety. We then analyze their implementation using the extended parallel processing model (EPPM). We show that, although threat of injury and death is used in the majority of these interventions to motivate individuals, the threat is inconsistent with the behaviors targeted. Other shortcomings and implications for implementing wide-scale farm work safety interventions are discussed.